Strategi Meningkatkan Hasil Belajar Ekonomi dengan Aplikasi Google Classroom pada Siswa Kelas XI IPS 1 SMAN 3 Kerinci - Rahmi Juita (Universitas Batanghari Jambi, 2022)
This study was an Action Research conducted because the student’s achievement on Mathematics was still lower than The minimum Achievement Criteria (KKM). Therefore, the researcher conducted a research to improve the student’s learning achievement by using Google classroom platform. This study aimed at figuring out whether the use of Google classroom could improve the student’s learning achievement on economics at grade XI IPS 1 SMAN 3 Kerinci in this pandemic Covid-19 era. This study had two cycles. Each cycle consists of planing, action, obsevation, and reflection. The analysis result showed that there was significant improvement on the student’s achievement. The student’s average score in pre cycle was 47,5 (28%) Then, in cycle 1 the score was 69 (64%), in cycle 2 it improved significantly to 80 ( 84%). Based on the data it concluded that the implementation of Google classroom platform improved the student’s achievement on economics subject significantly. It was suggested to economics teachers to apply the Google classroom platform as the alternative strategies in teaching.